Answer:
the first one is 113.04m
the second one is 615.44 cm
the third one is 530.66 ft
the fourth one is 163.28 in
the fifth one is 31.4 m
the sixth one is 28.26 m
the seventh one is 314
the eightth one is 50,24
finally finished:)))
If f(z)=m^z - n^z <span>and f(1)=2, f(2)=8
then
m - n = 2 so m = n + 2
m^2 - n^2 = 8
substitute </span>m = n + 2 into m^2 - n^2 = 8
so
m^2 - n^2 = 8
(n + 2)^2 - n^2 = 8
n^2 + 4n + 4 - n^2 = 8
4n = 4
n = 1
m = n + 2 = 1 + 2 = 3
so f(z) = 3^z - 1^z
if z = 1 the f(1) = 3^1 - 1^1 = 2
if z = 2 the f(2) = 3^2 - 1^2 = 9 - 1 = 8
if z = 3 the f(3) = 3^3 - 1^2 = 27 - 1 = 26
answer
f(3) = 26
The answer is 4565 / 63
Sorry this might be to late...
Answer:
6 and 7
Step-by-step explanation:
x + y = 13
xy = 42
I just listed the two equations out and the answer just popped out. The trick to this is just thinking about two numbers that obviously both below 13 that add up to it. 6 and 7 is the solution.